Changing of discursive strategies of international and local NGOs to block dam constructions: The Mesopotamian identity marker - László, Zsófia Jázmin (POLARITIES, 2025)
This article explores the evolving discursive strategies of international and local non-governmental organizations (NGOs) opposing the construction of the Ilisu Dam in Turkey in light of broader conflict dynamics in the Eastern Mediterranean. The Ilisu Dam, a cornerstone of Turkey’s Southeastern Anatolia Project (GAP), has sparked significant controversy because of its environmental, cultural, and socioeconomic ramifications, including large-scale displacement and the destruction of ancient sites. This study examines how NGOs have strategically reframed their opposition over time, incorporating arguments around human rights, cultural heritage, and international law to complement environmental advocacy. Central to this analysis is the Mesopotamian identity marker as a unifying discursive tool, which contrasts with the divisive nationalist rhetoric and aims to foster regional solidarity and international cultural engagement. Process tracing was employed to identify the critical stages of these strategic adaptations, highlighting the role of shifting geopolitical conditions, transnational alliances, and identity framing in influencing public perception and advocacy outcomes. The findings underscore how such strategies resonate with regional and global audiences, shaping cross-border support and pressuring external stakeholders. By situating the Ilisu Dam controversy within the context of regional conflicts over resources, identities, and governance, this article contributes to the understanding of how local and transnational actors navigate the complex intersections of environmental and socio-political challenges in the Eastern Mediterranean.